Anti- NMDAR Encephalitis in a 28 years old female: Revisited - Jha, Rajiv; Jalan, Pankaj; Shah, Rajiv; Chaturvedi, Adarsh (Nepal Journal of Neuroscience, 2023)
Anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis is the prevailing subtype of autoimmune encephalitis, commonly misdiagnosed initially as infectious encephalitis due to its symptomatology resembling that of viral encephalitis and meningitis. The condition exhibits a higher incidence in females, with a gender ratio of 4:1 compared to males. While electroencephalogram (EEG) and magnetic resonance imaging (MRI) aid in the diagnostic process, the presence of antibodies in the cerebrospinal fluid (CSF) serves as the definitive confirmation. Autoimmune encephalitis typically presents with a spectrum of neuropsychiatric symptoms